2017
DOI: 10.3892/br.2017.962
|View full text |Cite
|
Sign up to set email alerts
|

Morphine pre- and post-conditioning exacerbates apoptosis in rat hippocampus cells in a model of homocysteine-induced oxidative stress

Abstract: Abstract. Recent investigations indicated that morphine has protective effects in different ischemia/reperfusion models and may protect against neuronal cell death, while other evidence showed that morphine induces apoptosis in neurons. Therefore, the current study was conducted to investigate preand post-conditioning effects of morphine on hippocampal cell apoptosis in a rat model of homocysteine (Hcy)-induced oxidative stress. In the present study, 0.5 µmol/µl Hcy was injected into bilateral intrahipocampal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…It seems that the high dose of BHT, cause injury of the nervous tissue that was appeared in the brain tissue examination in our study which is agreement with Karkhah and et al (22) mention neuropathy led to the effects on the degree of animal interest in the environment has decreased and the length of time required for rotation in the avoidance of the high edge has been increased. Our explanation may be due to the hypothalamic pathway being affected, here is that the neural information follows the slow second pathway from the cerebral cortex to the amygdala, speed of information transmission is slower and takes longer and the response is slower than before (23), represented by delayed in avoid the edge of the slope.…”
Section: Discussionsupporting
confidence: 92%
“…It seems that the high dose of BHT, cause injury of the nervous tissue that was appeared in the brain tissue examination in our study which is agreement with Karkhah and et al (22) mention neuropathy led to the effects on the degree of animal interest in the environment has decreased and the length of time required for rotation in the avoidance of the high edge has been increased. Our explanation may be due to the hypothalamic pathway being affected, here is that the neural information follows the slow second pathway from the cerebral cortex to the amygdala, speed of information transmission is slower and takes longer and the response is slower than before (23), represented by delayed in avoid the edge of the slope.…”
Section: Discussionsupporting
confidence: 92%
“…This phenomenon was observed in microglial cells and macrophages [ 21 ]. Additionally, many experimental animal studies have shown that morphine increases markers of oxidative stress in the cerebral cortex and serum [ 22 ]. Moreover, significantly increased serum MDA and decreased SOD and CAT activity were observed during tramadol treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence suggests that parental morphine exposure exacerbates apoptosis and reduces pyramidal neurons in hippocampus (Ghafari and Golalipour, 2014[29]; Karkhah et al, 2017[39]). Another evidence revealed that morphine mediates the physiological changes in the synaptic plasticity in the hippocampus (Sarkaki et al, 2008[60]).…”
Section: Discussionmentioning
confidence: 99%